Medications and Bone Health: A Comprehensive Review of Skeletal Risks and Therapeutic Approaches - Pandi, Kaniga; Cheriyan, Binoy Varghese; Murali, Dharshan; Boobalan, Nesayan; Harikrishnan, Jeevitha; Kannan, Deepshikaa; Jebaraj, Lini Priyadharshini Christopher; Munuswamy, Shamyuktha; Manaksha, Shagul Hameed; Sekar, Sriharan; Palaniraja, Vimal; Sivagnanam, Naresh; et al. (International Journal of Pharmaceutical Investigation, 2026)
Bone-drug interactions represent a critical yet often under recognized domain within clinical pharmacology due to their long-term implications on skeletal integrity. The human skeletal system relies on a tightly regulated balance between bone formation and resorption. Disruption of this balance by commonly prescribed medications can result in reduced Bone Mineral Density (BMD), compromised bone structure, and an elevated risk of fractures. This review aims to evaluate the mechanisms, clinical consequences, and therapeutic strategies related to drug-induced bone disorders, focusing on widely used medications such as glucocorticoids, Antiepileptic Drugs (AEDs), Proton Pump Inhibitors (PPIs), chemotherapeutic agents, and hormonal therapies. Glucocorticoids suppress osteoblast function and enhance osteoclast activity, causing net bone loss. AEDs impair vitamin D and calcium metabolism via cytochrome P450 enzyme induction. PPIs reduce calcium absorption by altering gastric pH, affecting bone mineralization. Chemotherapeutic agents disrupt both osteoblast and osteoclast function, accelerating bone turnover. Hormonal therapies such as aromatase inhibitors and androgen deprivation therapy exacerbate bone loss, especially in oncology patients. High-risk groups include postmenopausal women, elderly individuals, and patients on chronic drug therapy. Conclusion: Bone-drug interactions significantly contribute to conditions like osteopenia, osteoporosis, and fragility fractures. Clinical management involves early detection using BMD tests and biochemical markers, lifestyle interventions (exercise, smoking cessation), and nutritional support (calcium and vitamin D). Pharmacological agents such as bisphosphonates, SERMs, and denosumab are effective in preventing drug-induced bone loss. Personalized medicine approaches especially those incorporating genetic risk profiling can optimize treatment decisions and minimize adverse skeletal outcomes. Multidisciplinary collaboration and further research into safer drug formulations and targeted therapies are vital to safeguard bone health in vulnerable populations.
Keywords: Bone-drug Interactions; Osteoporosis; Glucocorticoids; Bone Metabolism; Fracture Risk; Pharmacological Management.